MODELING, SIMULATION AND CONTROL IN PROCESS INDUSTRY AND ITS RELEVANT IMPORTANCE - Rehman, W.; Tahir, M. S. (The Nucleus, 2020)
Modeling is an important tool to study and evaluate the behavior of the chemical process. Combination of simulation and control, it exhibits various characteristics of the process and provides the right direction to obtain the desired results from the chemical reactors. This paper discusses the various technical aspects of modeling, simulation and control in the process industries. The utilization and the relationship among the three techniques, modeling, simulation and control have been discussed. A case study is then presented for a batch reactor (in a sugar manufacturing plant) to use the modern techniques for modeling, simulation and instrumentation control. Presenting various scenarios on the above discussed techniques, the task has been dealt with comprehensively.